Практико-ориентированная подготовка специалистов для горно-рудной промышленности - Скалозубова, Г.В. (My University, 2016)
An experience of a practice-oriented training in technical specialties in Rudny Industrial Institute. Indicate the main forms of cooperation with enterprises-employers.
Keywords: practice-oriented teaching; innovative educational programs; enterprise employers